Personal Development of Professional Teachers Total Quality Management (TQM) Approach in Improving the Quality of Education in SMP Negeri 2 Rantepao, Toraja Utara Regency - Emi Liku; Bintang Simbolon; Dameria Sinaga (Budapest International Research and Critics University, 2022)
This study uses a qualitative method with a research design that has 3 main constructs, namely self-development to improve professional competence with the Sheward's Cycle approach including Plan, Do, Check, and Act. The place of research is the State Junior High School 2 Rantepao, while the object of the research is certified teachers, totaling 52 teachers and 178 students as respondents whose function is to verify the answers to the interview results. The results of this study indicate that the quality of education at SMPN 2 Rantepao based on the report card of quality achievements for 3 years has decreased significantly, especially in the standard of graduate competence, content, process, and educational assessment. This is due to the lack of self-development of professional teachers who use Sheward's Cycle at each stage of self-development. The initial stage begins with self-acceptance for certified teachers with less than 7 years of teaching experience, the self-reflection stage for teachers with 8-15 years of teaching experience, the adjustment stage for teachers with 15-20 years of teaching experience, and the self-actualization stage for certified teachers with teaching experience. more than 20 years. Professional teacher self-development uses the assumptions of Abraham Maslow's hierarchy of needs theory and Theory Y developed by Douglas McGregor where self-adjustment and self-actualization needs are upper-level needs that can be met after the needs of adjustment and self-reflection as lower-level needs are met. The self-development of professional teachers has not run optimally, especially at the stage of adjustment and self-actualization of professional teachers. The indicator is that professional teachers are still conventional so carrying out professional duties is only limited to fulfilling the teaching load (24 hours of meetings). The non-optimal self-development of professional teachers has implications for the quality of teacher competencies that do not experience quality improvement both in terms of planning, implementation, analysis, and follow-up to the application of quality culture.